Rational Discourse in Pesantren Applying Habermas’s Critical Theory Philoshopy in Southeast Asia - Rofiq Hidayat; Brett Aaron Huggins; Abd. Haris; Baharuddin (IJIBS, 2026)
This study aims to analyze the application of Jürgen Habermas’s theory of communicative action in rational discourse practices within Southeast Asian pesantren (Islamic boarding schools). Employing a qualitative library research approach, this study examines scholarly literature from the past five years concerning pesantren, digital public spheres, and critical theory. The findings indicate that practices such as bahtsul masail and institutional discussions exhibit deliberative characteristics that approximate communicative rationality, particularly in testing validity claims through collective argumentation. Nevertheless, hierarchical structures between religious leaders and students remain a limiting factor in achieving the ideal speech situation. Digital transformation expands the pesantren public sphere into a more participatory transnational arena, although it introduces challenges such as polarization and regulatory constraints. The study concludes that pesantren can be conceptualized as a laboratory of critical theory praxis in a non-Western Islamic context, contributing to the enrichment and reconstruction of communicative action theory through Southeast Asian socio-religious experiences.